Anchoring: A valid explanation for biased forecasts when rational predictions are easily accessible and well incentivized? - Lukas Meub; Till Proeger; Kilian Bizer (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
Behavioral biases in forecasting, particularly the lack of adjustment from current values and the overall clustering of forecasts, are increasingly explained as resulting from the anchoring heuristic. Nonetheless, the classical anchoring experiments presented in support of this interpretation lack external validity for economic domains, particularly monetary incentives, feedback for learning effects and a rational strategy of unbiased predictions. We introduce an experimental design that implements central aspects of forecasting to close the gap between empirical studies on forecasting quality and the laboratory evidence for anchoring effects. Comprising more than 5,000 individual forecasts by 455 participants, our study shows significant anchoring effects. Without monetary incentives, the share of rational predictions drops from 42% to 15% in the anchor's presence. Monetary incentives reduce the average bias to one-third of its original value. Additionally, the average anchor bias is doubled when task complexity is increased, and is quadrupled when the underlying risk is increased. The variance of forecasts is significantly reduced by the anchor once risk or cognitive load is increased. Subjects with higher cognitive abilities are on average less biased toward the anchor when task complexity is high. The anchoring bias in our repeated game is not influenced by learning effects, although feedback is provided. Our results support the assumption that biased forecasts and their specific variance can be ascribed to anchoring effects.
Keywords: C90; D03; D80; G17; 330; anchoring; cognitive ability; forecasting; heuristics and biases; incentives; laboratory experiment